The Local Wisdom Value in Baode Manuscript of The Banggai Tribe: A Semiotic Analysis - Nuriyati Samatan; Agung Prasetyo Wibowo; Renny Nur’ainy; Nuraeni Abdullah; Yohanes Ari Kuncoroyakti (ITScience (Information Technology and Science), 2022)
The purpose of the study is to analyze the Baode manuscript, as part of the local wisdom value of the Banggai Tribe through Semiotic Theory. This research is qualitative research, using a critical paradigm through semiotic analysis of the Baode manuscript, which is also called the twilight song as part of the local wisdom of the Banggai Nation. The Baode manuscript is divided into nine parts, each of which represents a signifier and a signified. The results of the show that the original Banggai tribe is what is currently called the Sea-Sea. From this, Sea Sea tribe was born and spread the Banggai Tribe known today. Thus, calling Sea-Sea is the same as calling the Banggai Tribe. The difference is only in their domicile. Therefore, it can be concluded that Baode is one of the non-material local wisdom of the Banggai tribe, whose existence is still preserved by the Banggai community. Baode is a shared identity that build collective awareness, even though they live apart by distance and time as well as the beliefs they hold.